Análise de estruturas no estado plano de tensões e deformações com materiais elásticos, ortótropos e não lineares - Obino Neto, Artur (1975)
Structural analysis for elastic-materials with non-linear constitutive equations. The principle of stationary energy is shown under weaker conditions than the usual assumption of a generalized Hooke's law. The finite element method is used for solving plane stress and plane strain problems. This method leads to a system of non-linear equations, which requires an incremental-iterative procedure to achieve the solution. The theory is applied to concrete structures, assuming that the material behaves according to the C.E.B. standards. The analysis was performed increasing the external forces until the colapse of the structure, assuming the Coulomb-Mohr covering for compression and the maximum stress criterion for tension stresses.